Correlation between Surgical Outcome and Stage of Acquired Middle Ear Cholesteatoma: Revalidation of the EAONO/JOS Staging System - Ardıç, Fazıl Necdet (J Int Adv Otol, 2020)
OBJECTIVES: This study aimed to evaluate the intraoperative findings, recurrence rate, and hearing outcome of cholesteatoma surgery and correlate them with the newly proposed EAONO/JOS Joint Consensus Statement. MATERIALS AND METHODS: The records of 407 patients diagnosed with chronic otitis media and cholesteatoma between 2009 and 2017 were reviewed. After the exclusion of records with unsatisfactory surgical notes and anamnesis, 353 patients were included in the study. The 290 patients who had undergone primary surgery and 63 who had undergone revision surgery were evaluated separately. RESULTS: Total 162 of 290 (56%) patients had retraction pocket cholesteatoma and 128 of 290 (44%) patients had non-retraction pocket cholesteatoma. Eighty (28%) patients had stage I, 114 (39%) had stage II, 91 (31%) had stage III, and 5 (2%) had stage VI disease. The recurrence rate was 6.9% (20/290). The average age of these patients at the time of the second operation was 23.31±10.3 years. Twelve patients had (60%) recurrent cholesteatoma, and eight (40%) had residual cholesteatoma. Hearing outcome and surgical technique were significantly associated with the disease stage; however, the recurrence rate showed no such association. CONCLUSION: We concluded that the EAONO/JOS staging system is beneficial for estimating the postoperative hearing results and planning the surgical technique. However, there was no significant relationship between the recurrence rate and the EAONO/JOS staging system. We believe that additional factors, such as infection, ossicles, and invasion, predict the recurrence. Widespread use of the EAONO/JOS staging system will enable better evaluation of surgical outcomes and prognosis.